Islamic Housing Projects and Environmental Awareness: Investigating the Concepts and Implementations Behind the Notion of ‘Islamic Environment’ - Rahmah, Sukmayati; Putrie, Yulia Eka; Handryant, Aisyah Nur; Maslucha, Luluk (Journal of Islamic Architecture, 2025)
Islamic housing developments have been more popular in recent years, driven by a wide range of contributing factors, including religious, economic, and socio-cultural considerations. The widespread availability of Islamic mortgages from Islamic banks and finance institutions also contributed to the rise of the Islamic housing market for people looking to buy a house while complying with Islamic principles. One of the key selling aspects of Islamic housing projects is their notion of an ‘Islamic Environment,’ which implies sustainability in the social and natural environments. However, mass housing projects’ emphasis on market demands and financial viability often sets aside broader social and ecological considerations in their implementations. These phenomena have raised a question of how the Islamic housing projects conceptualized and implemented this notion of an ‘Islamic Environment.’ An exploratory study was conducted by analyzing qualitatively and quantitatively visual and text data from interviews, field observations, architectural drawings, and marketing materials. The findings showed that at the conceptual level, a partial understanding of Islamic values of environmental awareness is still the main issue that also impacted the implementations at the practical level. The understanding of the Islamic environment is limited to the socio-religious environment in the form of providing places of worship and religious activities. At the practical level, the selling point of the green atmosphere is still limited to the visual pleasures of the distant mountains and gardens outside the residential area. Hence, efforts to rethink the concept and application of the Islamic environment are imperative to ensure genuine environmental sustainability, and ‘nature’ transcends being merely a marketing strategy for Islamic housing projects. Keywords:housing projects, Islamic environment, sustainability, concept, implementation